Hip Replacement after Proximal Femur Failed Osteosynthesis: our experience - Corradi, Nicola; Caruso, Gaetano; Martini, Ilaria; Massari, Leo (Acta Biomedica Atenei Parmensis, 2022)
Background and aim: failure of proximal femur fixation is a rare but challenging complication. Hip replacement could be a safe and optimal salvage treatment option. However, serious complications could occur. The aim of our study is to retrospectively review all hip replacement performed after proximal femur fixation failure and to evaluate functional and radiographic outcomes.Methods: we reviewed all Total Hip Arthroplasty and Hemiarthroplasty performed from 2013 to 2020 in Our Departement. We evaluated latest follow-up x-rays for stem subsidence, varus-valgus stem position (>5°), limb lenght inequality (>1cm), dislocation, component loosening, heterotopic calcification classified according to Brooker, cement leakage. Harris Hip Score (HHS) and Hip WOMAC score were perfomed at the latest follow-up to estimate functional outcome.Results: 14 THA had no complications with mean HHS 86.5 and WOMAC score 91,68. 1 periprosthetic infection was reported on THA, however after 2-stages revision functional and radiographic otucomes were satisfactory. 5 HA had rated mean HHS 65.8 and WOMAC score 70.18. 2 HA experienced dislocations which required surgical revision and conversion to THA.Conclusions: as a salvage surgery for failure of proximal femur fixation, Hip Replacement is safe and recommendable. THA reported better results than HA. Nonetheless, every patient should be carefully evaluated before undergoing surgery to detect possible complication risk factors